Integrated de novo Analysis of Transcriptional and Metabolic Variations in Salt-Treated Solenostemma argel Desert Plants - Ahmad, Hasan; Maher, Mohamed; Abdel-Salam, Eslam M.; Li, Yufei; Yang, Chenkun; ElSafty, Nagwa; Ewas, Mohamed; Nishawy, Elsayed; Luo, Jie (Frontiers in Plant Science, 2021)
Solenostemma argel (Delile) Hayne is a desert plant that survives harsh environmental conditions with several vital medicinal properties. Salt stress is a major constraint limiting agricultural production around the globe. However, response mechanisms behind S. argel plants adaptation to salt stress are still poorly understood. In the current study, we applied an omics approach to explore how this plant adapts to salt stress by integrating transcriptomic and metabolomic changes in roots and leaves of S. argel plants under salt stress. De novo assembly of transcriptome produced 57,796 unigenes represented by 165,147 transcripts/isoforms. A total of 730 DEGs were identified in roots (396 and 334 were up- and down-regulated, respectively). In leaves, 927 DEGs were identified (601 and 326 were up- and down-regulated, respectively). GO and KEGG pathway enrichment analyses revealed that several defense-related biological processes such as response to osmotic and oxidative stress, hormonal signal transduction, MAPK signaling, and phenylpropanoid biosynthesis pathways are potential mechanisms involved S. argel plants tolerance to salt stress. Furthermore, liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to detect metabolic variations of S. argel leaves and roots under control and salt stress. Forty-five and fifty-six critical metabolites showed changes in levels in stressed roots and leaves, respectively; there were 20 metabolites in common between roots and leaves. Differentially accumulated metabolites included amino acids, polyamine, hydroxycinnamic acids, monolignols, flavonoids, and saccharides that improve antioxidant ability and osmotic adjustment of S. argel plants under salt stress. The results present insights into potential salt response mechanisms in Sargel desert plants and increase the knowledge in order to generate more tolerant crops to salt stress.